Description and Solution of an Unreported Intrinsic Bias in Photon Mapping Density Estimation with Constant Kernel - García, R.; Ureña, C.; Sbert, M. (Computer graphics forum, 2012)
This paper presents an analysis of the irradiance estimator often used in photon mapping algorithms and concludes that the classical approach with a constant kernel overestimates the correct value. We propose a new estimator that solves this problem and provide both theoretical and empirical studies to verify it.